No future: Queer theory and the death drive - Edelman, Lee (Duke University Press., 2004)
In this searing polemic, Lee Edelman outlines a radically uncompromising new ethics of queer theory. His main target is the all-pervasive figure of the child, which he reads as the linchpin of our universal politics of “reproductive futurism.” Edelman argues that the child, understood as innocence in need of protection, represents the possibility of the future against which the queer is positioned as the embodiment of a relentlessly narcissistic, antisocial, and future-negating drive. He boldly insists that the efficacy of queerness lies in its very willingness to embrace this refusal of the social and political order. In No Future, Edelman urges queers to abandon the stance of accommodation and accede to their status as figures for the force of a negativity that he links with irony, jouissance, and, ultimately, the death drive itself. Closely engaging with literary texts, Edelman makes a compelling case for imagining Scrooge without Tiny Tim and Silas Marner without little Eppie. Looking to Alfred Hitchcock’s films, he embraces two of the director’s most notorious creations: the sadistic Leonard of North by Northwest, who steps on the hand that holds the couple precariously above the abyss, and the terrifying title figures of The Birds, with their predilection for children. Edelman enlarges the reach of contemporary psychoanalytic theory as he brings it to bear not only on works of literature and film but also on such current political flashpoints as gay marriage and gay parenting. Throwing down the theoretical gauntlet, No Future reimagines queerness with a passion certain to spark an equally impassioned debate among its readers
Keywords: amériques; approches et analyses; cinéma; communication; cours; cycles supérieurs; discipline; fem1000; fem7000; lit2815; lit3220; lit3495; premier cycle; psychanalyse; queer; régions géographiques; sciences humaines; thématiques; violences; états-unis; études culturelles

Female subjects in black and white: Race, psychoanalysis, feminism - Abel, Elizabeth; Christian, Barbara; Moglen, Helene (University of California Press, 1997)
This landmark collaboration between African American and white feminists goes to the heart of problems that have troubled feminist thinking for decades. Putting the racial dynamics of feminist interpretation center stage, these essays question such issues as the primacy of sexual difference, the universal nature of psychoanalytic categories, and the role of race in the formation of identity. They offer new ways of approaching African American texts and reframe our thinking about the contexts, discourses, and traditions of the American cultural landscape. Calling for the racialization of whiteness and claiming that psychoanalytic theory should make room for competing discourses of spirituality and diasporic consciousness, these essays give shape to the many stubborn incompatibilities―as well as the transformative possibilities―between white feminist and African American cultural formations. Bringing into conversation a range of psychoanalytic, feminist, and African-derived spiritual perspectives, these essays enact an inclusive politics of reading. Often explosive and always provocative, Female Subjects in Black and White models a new cross-racial feminism.
Keywords: afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; femmes* afro-américaines; féminismes noirs; littérature; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences humaines; états-unis; études littéraires

Feminities, masculinities, sexualities: Freud and beyond - Chodorow, Nancy J. (The University Press of Kentucky, 1994)
La psychanalyse peut-elle aller au-delà d'une vision monolithique du genre et de la sexualité normale pour aborder les questions de diversité et de variabilité dans le développement du genre et l'identité de genre ? Ses praticiens et théoriciens peuvent-ils rendre des comptes rendus non pathologisants de la variation de l'orientation sexuelle ? S'appuyant sur une lecture attentive des textes psychanalytiques commençant par Freud et sur sa propre expérience clinique, Chodorow [soutient] que la psychanalyse doit encore démêler la domination masculine de l'hétérosexualité. Elle démontre également le manque de compréhension psychanalytique de l'hétérosexualité et la polarisation problématique des sexualités normales et anormales. Chodorow soutient que la psychanalyse doit prêter attention à la spécificité individuelle et au cadre personnel, culturel et social
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; domination masculine; fem1000; genre; hétérosexisme; hétérosexualité; identités LGBTQIA2+; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis

The daughter's seduction: Feminism and psychoanalysis - Gallop, Jane (Cornell University Press, 1982)
At the time this book was published in 1982, Jane Gallop was professor of French at Miami University; she has also written Intersections: A Reading of Sade with Bataille, Blanchot, and Klossowski. She wrote in the Introduction, "[the book] studies the relation between contemporary feminist theory and the psychoanalysis of Jacques Lacan... it enters into a network of problems: problems of sexual difference, of desire, of reading, or writing, of power, of family, of phallocentrism and of language... this book is ... a contribution to the sort of thinking it describes---that is, a contribution to French psychoanalytic feminist thought from the vantage point of these English-speaking shores." (p.11) She adds, "The book begins by calling into question certain feminist assumptions through the agency of Lacanian psychoanalysis. It ends by calling into question certain psychoanalytic positions through the agency of feminist writing." (p.15) She states that "[Freudian] Phallocentrism seems wrong to [Ernest] Jones: that is, immoral by virtue of being 'excessive, immoderate,' which is to say, unreconcilable with a 'sense of proportion.' The phallic disproportion brings him... to champion the claims of an 'underestimated' female sexuality to a more balanced, more proportionate estimate. His 'sense of proportion,' his spirit of fair play, will be sufficiently scandalized to provoke his only major departure from Freud's theory." (p. 16) She observes that in an article, "[Stephen] Heath begins by informing us that ... Lacan's 1972/73 seminar [is] devoted to 'what Freud expressly left aside... What does woman want?' ... Yet Lacan said nothing of devotion... Lacan speaks of a beginning... of a relation to this question: far from devoting himself to women he is simply at the stage of approach, first and rather aggressive encounter." (p. 43) This book will be of interest to feminists studying psychoanalysis, or to students of Lacan.
Keywords: 1900-1999; amériques; cours; discipline; fem1000; premier cycle; psychanalyse; périodes historiques; régions géographiques; sciences; sciences humaines; thématiques; écriture des femmes*; états-unis

The reproduction of mothering: psychoanalysis and the sociology of gender - Chodorow, Nancy (University of California Press, 1978)
When this best-seller was published, it put the mother-daughter relationship and female psychology on the map. The Reproduction of Mothering was chosen by Contemporary Sociology as one of the ten most influential books of the past twenty-five years. With a new preface by the author, this updated edition is testament to the formative effect that Nancy Chodorow's work continues to exert on psychoanalysis, social science, and the humanities.
Keywords: 1900-1999; amériques; cours; cycles supérieurs; discipline; fem1000; fem9000; figure de la mère; genre; identités LGBTQIA2+; maternité; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; états-unis

Visual Pleasure and Narrative Cinema - Mulvey, Laura (Screen, 1975)
Cet article se propose d'utiliser la psychanalyse pour découvrir où et comment la fascination du film est renforcée par des schémas de fascination préexistants déjà à l'œuvre au sein du sujet individuel et des formations sociales qui l'ont façonné. Il prend pour point de départ la façon dont le cinéma reflète, révèle et même joue sur la lecture droite et socialement établie de la différence sexuelle qui commande les images, les regards érotiques et le spectacle. Il est utile de comprendre ce qu'a été le cinéma, comment sa magie a opéré dans le passé, tout en tentant une théorie et une pratique qui remettront en cause ce cinéma du passé. La théorie psychanalytique est ainsi appropriée ici comme une arme politique, démontrant la manière dont l'inconscient de la société patriarcale a structuré la forme cinématographique.
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cinéma; cours; discipline; fem1000; fem3200; male gaze; premier cycle; privilèges; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences; sciences humaines; sofia; systèmes d'oppressions; états-unis

Peau noire, masques blancs - Fanon, Frantz (Seuil, 1971)
La décolonisation faite, cet essai de compréhension du rapport Noir-Blanc a gardé toute sa valeur prophétique : car le racisme, malgré les horreurs dont il a affligé le monde, reste un problème d'avenir. Il est ici abordé et combattu de front, avec toutes les ressources des sciences de l'homme et avec la passion de celui qui allait devenir un maître à penser pour beaucoup d'intellectuels du tiers monde.
Keywords: 1900-1999; 1950-1959; amériques; antilles; approches et analyses; colonialisme; cours; discipline; décolonialisme; europe; fem1000; femmes* noires; france; féminisme décolonial; har4600; histoire; postcolonialisme; premier cycle; psychanalyse; périodes historiques; racisme; régions géographiques; sciences; sciences humaines; systèmes d'oppressions